The long-term risk of smoking in diabetic patients with stable ischemic heart disease treated with intensive medical therapy and lifestyle modification. (29th August 2020) - Khan, Asrar A; Chung, Matthew J; Novak, Eric; Mori Brooks, Maria; Brown, David L
Abstract: Introduction: The long-term risk of smoking in diabetic patients with stable ischemic heart disease (SIHD) is unknown. We sought to analyze the impact of smoking on outcomes of diabetic patients with SIHD when other cardiovascular risk factors are being aggressively treated. Methods: The Bypass Angioplasty Revascularization Investigation 2 Diabetes (BARI 2D) trial randomized 2368 diabetics with SIHD to intensive medical therapy (IMT) with prompt revascularization or IMT alone. Smoking status was obtained at baseline, 6 months, and 1, 2, 3, 4 and 5 years. The primary endpoint of interest was all-cause mortality. Results: Of 2360 patients, 33.1% of patients never smoked, 54.4% were former smokers, and 12.5% were current smokers. The rate of all-cause mortality was greater for current (2.5 deaths/100 patient-years) and former smokers (3.1 deaths/100 patient-years) than never smokers (2.1 deaths/100 patient-years) (P = 0.007). Cardiac death, cardiovascular death, fatal or nonfatal myocardial infarction, and fatal or nonfatal stroke were not increased in current or former smokers compared with never smokers. Compared with never smokers, current smokers experienced a 49% increased hazard of death (Hazard Ratio (HR) 1.49, 95% Confidence Interval (CI): 0.97–2.29, P = 0.07) whereas former smokers had a 37% increased hazard of death (HR 1.37, 95% CI: 1.04–2.79, P = 0.02) when considering smoking status as a time-dependent variable and adjusting for factors that differed by smoking status. Conclusions: Current and former smoking are associated with increased all-cause mortality in diabetics with SIHD but not with increased cardiovascular morbidity or mortality.